Análise de malhas de aterramento compostas por eletrodos verticais profundos em torres de linhas de transmissão - Raphael Batista Borges Louro (2020)
This work presents a study on the use of deep vertical electrodes as an alternative to the typical grounding mesh of transmission line towers, particularly related to stratified soil conditions. The approximated model for the soil from Minas Gerais presents a higher electrical resistivity related to the first-layer compared to the second-layer. This finding suggests the study of deep vertical electrodes as a grounding configuration in similar situations in order to achieve lower impulsive impedance values. Models based on the transmission line theory have their expression developed as well as the implementation of the problem on commercial programs that solve full-wave Maxwell equations. These techniques are evaluated to solutions provided by other works, aiming to validate further research analysis. The text presents a proposal for the installation of deep vertical electrodes, including technical details of construction and cost; comparisons of the impulsive response of the evaluated grounding meshes as well as configurations composed of counterpoise wires and vertical electrodes; deductions and conclusions regarding the use of expressions from models related to the frequency-dependence of electrical resistivity and permittivity of the soil in conditions of stratified medium; beyond a case study carried out on a 230 kV transmission line. The results show good accuracy with other works and suggest the technical and economic feasibility of using deep vertical electrodes, especially when compared to the installation of transmission line surge arresters. For a critical path of the evaluated transmission line, the lightning performance of the deep vertical electrodes seems to be very suitable, in addition to being three times cheaper than the surge arresters’ option. Other advantages of the proposed procedure are the small land area for its installation, high toughness in relation to conductors stealing, easy control of the developed electric potential on the soil surface and the possibility of being used in combination with other techniques that improve transmission lines performance.